Competences in mother-tongue of young immigrants at school – a neglected resource in German schools - Bär, Christine (Glottodidactica, 2010)
The article deals with the influence which have the competences in mother tongue on the second language acquisition. Furthermore it is about the possibilities to apply these competences to German as a second language by young immigrants at school. Along with the theoretical expositions the author shows some implications for scholar instruction by using the mother tongue as a resource to acquire a second language.